2010
DOI: 10.1089/sur.2010.023
|View full text |Cite
|
Sign up to set email alerts
|

Re-Laparotomy for Severe Intra-Abdominal Infections

Abstract: Further work to develop more specific clinical tools and criteria to improve the accuracy of diagnosis may lead to use of the laparotomy-on-demand strategy rather than planned re-laparotomy. At this time, there is no good clinical evidence to support one strategy over the other from a mortality standpoint.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 14 publications
1
8
0
Order By: Relevance
“…The Ethiopian study demonstrated that neonatal age (< 1 month) was found to be an independent risk factor for death following pediatrics re-laparotomy (p=0.013) (7). This study and many other studies did not show any significant difference in mortality which supports the choice of PRL and ODRL one over the other (3,4,10,12,19). Literatures also reported that ODRL did have a substantial reduction in re-laparotomies, healthcare utilization including ICU, and medical costs (4,19).…”
Section: Discussionsupporting
confidence: 60%
“…The Ethiopian study demonstrated that neonatal age (< 1 month) was found to be an independent risk factor for death following pediatrics re-laparotomy (p=0.013) (7). This study and many other studies did not show any significant difference in mortality which supports the choice of PRL and ODRL one over the other (3,4,10,12,19). Literatures also reported that ODRL did have a substantial reduction in re-laparotomies, healthcare utilization including ICU, and medical costs (4,19).…”
Section: Discussionsupporting
confidence: 60%
“…15,20,21,24,28 The risks and benefits of relaparotomy in the setting of intra-abdominal infections have been well described in the literature evaluating the optimum timing for such intervention. 1,29,30 Early reintervention allows for prompt detection of infectious foci, minimal postoperative adhesions, and early source control. With a negative relaparotomy rate of nearly 30 per cent in ondemand procedures, 1,29,31 risks include exposure to potentially unnecessary surgery and anesthesia, increased adhesions, higher costs, and exaggerated physiological response, which may predispose patients to developing multiorgan failure.…”
Section: Discussionmentioning
confidence: 99%
“…1,29,30 Early reintervention allows for prompt detection of infectious foci, minimal postoperative adhesions, and early source control. With a negative relaparotomy rate of nearly 30 per cent in ondemand procedures, 1,29,31 risks include exposure to potentially unnecessary surgery and anesthesia, increased adhesions, higher costs, and exaggerated physiological response, which may predispose patients to developing multiorgan failure. 1,32 On the other hand, if an abscess can be detected, accessed, and undergo successful percutaneous catheter placement, many of these concerns are avoided.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Planned relaparotomy consistently generated more costs across the whole range of different courses of disease. Katherine Mandell and Saman Arbabi [29]. The role of relaparotomy in the management of intra-abdominal infection remains controversial.…”
Section: Vmentioning
confidence: 99%